2016
DOI: 10.1038/srep33040
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of docosahexaenoic acid nanoemulsion on erectile function in a rat model of bilateral cavernous nerve injury

Abstract: There is an unmet need for treatment of erectile dysfunction resulting from radical prostatectomy and cavernous nerve (CN) injury. Given the neuroprotective properties of docosahexaenoic acid (DHA), we investigated its effect on penile functional and structural recovery in a rat model of bilateral cavernous nerve injury. Rats were subject to CN injury and received intraperitoneal administration of either vehicle or a DHA nanoemulsion (nano-DHA) at 10, 50, or 250 μg/kg. Functional testing and histological analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…Our results showed that the nNOS content in both the MPG and the dorsal penile nerve was reduced in the CN traction group, which is consistent with results in other CN injury models [9,24,25]. The number of neurofilament-positive nerve fibers in the dorsal penile nerve also declined, indicating that the axon contents were decreased after CN traction, which is also consistent with previous studies [26,27]. These findings suggest that CN traction could impair erectile function by reducing both the total number of nerve fibers and the number of nNOS-positive nerve fibers in the dorsal penile nerve.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the nNOS content in both the MPG and the dorsal penile nerve was reduced in the CN traction group, which is consistent with results in other CN injury models [9,24,25]. The number of neurofilament-positive nerve fibers in the dorsal penile nerve also declined, indicating that the axon contents were decreased after CN traction, which is also consistent with previous studies [26,27]. These findings suggest that CN traction could impair erectile function by reducing both the total number of nerve fibers and the number of nNOS-positive nerve fibers in the dorsal penile nerve.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the elevated NOx level after application of the NE with NO is safe and only affects penile erection. Further safety investigation (e.g., tissue sectioning and image analysis using alternative animal experiments) can strengthen our conclusion 21 .…”
Section: Resultssupporting
confidence: 56%
“…S-nitrosylation of nNOS and the consequent decrease in this enzyme's activity has been documented in primary cortical and hippocampal neurons (35,45) and brainstem (46). Our findings imply that S-nitrosylation mainly affects eNOS and its downstream signaling in the neuropathic penis induced by cavernous nerve injury, while other modifications of nNOS, such as decreased synthesis (8,13,14,47,48) may be primarily responsible for neurogenic ED in this condition. It is also possible that nNOS is S-nitrosylated in the neuropathic penis but to a smaller extent than eNOS, making this posttranslational modification hard to detect with available techniques.…”
Section: Discussionmentioning
confidence: 53%